Meaningful Synergy in E-learning Integrating Environmental Awareness and Project-Based Learning in EFL - Zunaidah, Asih (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The study investigates EFL e-learning project-based education and environmental awareness. Despite limited participation and technology concerns, e-learning is evolving. This study supports